2017
DOI: 10.3899/jrheum.170421
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Canadian Core Clinical Dataset to Support High-quality Care for Canadian Patients with Rheumatoid Arthritis

Abstract: Objective.To develop a Canadian Rheumatoid Arthritis Core Clinical Dataset (CAN-RACCD) to standardize documentation encouraging high-quality care.Methods.A set of candidate elements was drafted through meetings with 27 rheumatologists, researchers, and patients, and supplemented with focused literature reviews. A 3-round online-modified Delphi consensus process was held with rheumatologists (n = 26), allied health professionals (n = 7), and patients (n = 4); for the remainder there was no demographic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 41 publications
0
23
0
2
Order By: Relevance
“…Although they recommended measuring quality of life and function, specific subdomains were not proposed (5). Barber et al in Canada also proposed a core set of measures to be collected in clinical practice to improve quality of care, rather than for longitudinal outcome studies (6).
We identified 88 prospective long‐term observational studies and registries across the world reporting outcomes in patients with rheumatoid arthritis. Globally, there is significant heterogeneity of collected and reported outcomes across observational studies and registries, varying according to the type of registry (i.e., disease‐based versus therapy‐based). Patient‐centered outcomes measuring symptom burden and mental and social aspects of disease are not consistently collected and/or reported.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they recommended measuring quality of life and function, specific subdomains were not proposed (5). Barber et al in Canada also proposed a core set of measures to be collected in clinical practice to improve quality of care, rather than for longitudinal outcome studies (6).
We identified 88 prospective long‐term observational studies and registries across the world reporting outcomes in patients with rheumatoid arthritis. Globally, there is significant heterogeneity of collected and reported outcomes across observational studies and registries, varying according to the type of registry (i.e., disease‐based versus therapy‐based). Patient‐centered outcomes measuring symptom burden and mental and social aspects of disease are not consistently collected and/or reported.
…”
Section: Introductionmentioning
confidence: 99%
“…A few studies examining the features of selected registries/LOS in RA have found significant heterogeneity in the outcomes collected, creating challenges in the comparability of findings across studies (1)(2)(3). Although there have been efforts to reduce the variability in data collection and analysis, a well-defined and universally accepted core set of outcomes to be measured in LOS that includes important patient-centered domains with specific relevance to long-term outcomes has yet to be agreed upon (4)(5)(6). The European Alliance of Associations for Rheumatology proposed a core set that primarily included pathophysiologic measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search was conducted in the electronic databases O projeto QualiTB visa desenvolver e validar metodologia de avaliação dos serviços de referência de nível secundário e terciário para tratamento ambulatorial da tuberculose no SUS, contribuindo com as iniciativas de monitoramento, avaliação e incremento da qualidade da atenção em tuberculose. Baseia-se em metodologias consagradas do campo [2,3] e na experiência anterior da equipe de pesquisa com serviços especializados em aids, Qualiaids [4][5][6] e da atenção básica, QualiAB [7,8].…”
Section: Introductionunclassified
“…Todos foram publicados em língua inglesa, e sete estão disponíveis em inglês e português. Os estudos se dedicaram à África(14), Ásia (13), América do Sul (10), Europa (2) e América do Norte(2). Seis estudos tinham abrangência intercontinental.Foram incluídos dois ensaios controlados randomizados[49][50], cinco revisões sistemáticas[36][51] incluindo três com metanálises [52][53][54], quatro caso controles [55][56][57][58]; quatro coortes [59][60][61][62], 10 estudos transversais [63-72], três quantitativos descritivos [73][74][75], uma revisão de literatura [76], cinco intervenções [77-80], oito estudos qualitativos [81-88] e quatro estudos de métodos mistos [89][90][91][92].…”
unclassified